Application of essential oil as a sustained release preparation in food packaging. (October 2019) - Ju, Jian; Chen, Xueqi; Xie, Yunfei; Yu, Hang; Guo, Yahui; Cheng, Yuliang; Qian, He; Yao, Weirong
Abstract: Background: Aromatic essential oils (EO) are important plant extracts that have attracted great interest for their various biological activities and their potential to replace chemical preservatives in the field of food preservation. Moreover, the volatility of EOs has further expanded their applications in antibacterial packaging (AP) systems. Scope and approach: This review focuses on the contributions of EOs to food packaging by (1) introducing the antibacterial activity of EOs; (2) summarizing the implementation of EO-APs; (3) analyzing the applications of EO-APs in food preservation; and (4) assessing the safety of EOs. Key findings and conclusions: Understanding the different combinations of EOs and food packaging will help improve the effectiveness of EO-APs in food preservation and better target their use, which will promote their application in food systems. By combining them with packaging materials, the adverse flavor of EOs can be reduced and their action time prolonged, which will greatly improve their effective utilization rate in food preservation. Highlights: Essential oils can be used as ingredients of active food packaging. Introduced the main active ingredients and antibacterial effects of EOs commonly used in food preservation. Focused on summarizing the implementation of EOs-AP. Analyzed the application of EOs-AP in food preservation.